2010
DOI: 10.1007/s11552-010-9303-7
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Suture Ligation Ablation for Ulnar Polydactyly: A Report of Two Cases

Abstract: We report two cases resulting in complications following suture ligation treatment for ulnar polydactyly. One case consisted of bilateral, retained gangrene and cellulitis, and a second case consisted of a residual, sensitive skin tag. The case involving gangrene and cellulitis developed after an unsuccessful suture ligation of bilateral pedunculated duplicated digits. The second case developed after suture ligature ablation of a rudimentary digit in the nursery but presented 3 years later with a residual symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Table 3 outlines their study design, OCEBM level of evidence, and alternative sources of bias. Carpenter et al 16 No complications Katz and Linder 17 No complications Leber and Gosain 11 No complications Mullick and Borschel 18 No complications Patillo and Rayan 19 No complications Singer et al 20 Flat scar (90%) Residual nubbins (10%) Comparative analyses…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 3 outlines their study design, OCEBM level of evidence, and alternative sources of bias. Carpenter et al 16 No complications Katz and Linder 17 No complications Leber and Gosain 11 No complications Mullick and Borschel 18 No complications Patillo and Rayan 19 No complications Singer et al 20 Flat scar (90%) Residual nubbins (10%) Comparative analyses…”
Section: Resultsmentioning
confidence: 99%
“…11,[16][17][18][19][20] Five studies reported no acute or long-term complications following surgical excision. 11,[16][17][18][19] Of these 5, the largest case series consisted of 26 patients (38 digits), and the longest follow-up time was 6 years. In a popular study, Leber and Gosain retrospectively analyzed surgical excision.…”
Section: Surgical Excisionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost of printing color figures is the responsibility of the author.In general, authors of case reports should use the Brief Report format.Volar Flap Closure of a Broad-based Supernumerary Finger simple cases such as the development of painful neuroma and surgical site infection. 1,2…”
mentioning
confidence: 99%
“…Volar Flap Closure of a Broad-based Supernumerary Finger simple cases such as the development of painful neuroma and surgical site infection. 1,2…”
mentioning
confidence: 99%